К сравнительно-анатомическому и функциональному анализу поясничного отдела позвоночника некоторых млекопитающих - Пылыпчук, О.Я. (Вестник зоологии, 1975)
The article deals with certain results of comparative-anatomical analyses and morphometry of bone, cartilage and ligament apparatuses of the lumbar region in certain mammals and with an attempt of their biomechanical analysis.